2011
DOI: 10.1007/s12600-011-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different solarizing materials on weed suppression and lettuce response

Abstract: The effect of four solarizing plastic materials on weed suppression and yield response of two lettuce cultivars ('Bacio' and 'Moringa') grown during two consecutive seasons was investigated at Metaponto (40°2 3′N; 16°47′E; 10 ma.s.l.), southern Italy. All solarization treatments suppressed winter and summer weeds with no significant difference among the plastic materials, although biodegradable film was less efficient in controlling common purslane and common amaranth. Weed infestation at the harvest of both l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Earlier researchers revealed that as soil temperature increased, weed germination was reduced significantly [32] [33]. An experiment conducted by [34] which testing 4 different mulches, i.e. EVA, LDPE, COEX, and BDP on lettuce confirmed that soil solarization was capable of suppressing the weed growth.…”
Section: Resultsmentioning
confidence: 82%
“…Earlier researchers revealed that as soil temperature increased, weed germination was reduced significantly [32] [33]. An experiment conducted by [34] which testing 4 different mulches, i.e. EVA, LDPE, COEX, and BDP on lettuce confirmed that soil solarization was capable of suppressing the weed growth.…”
Section: Resultsmentioning
confidence: 82%
“…It may also control S. halepense rhizomes through the solarization effect (Law et al 2008). Tarping can raise surface soil temperatures to over 60 C in the summer (Candido et al 2012) and 45 C in the fall (Horowitz et al 1983). Solarization has been used to control several weed species in vegetable production systems, including perennials such as nutsedges ( Cyperus spp.)…”
Section: Resultsmentioning
confidence: 99%
“…Soil solarization is a technique in which the soil, moistened and mulched with a transparent plastic film, is heated by solar radiation for several days up to thermal levels lethal or injurious for soilborne pests [3]. On the other hand, biofumigation consists of soil solarization in which some organic matrix is added to have both the release of biocidal gases, such as alcohols, aldehydes, sulfides and isothiocyanates, resulting from the degradation of soil organic amendments, and to have some biostimulant or biofertilizer effects [4][5][6].…”
Section: Introductionmentioning
confidence: 99%